Workers cooperatives in software and computer services: subversion to cognitive capitalism? - Zanotti, Agustín (2016)
The software and informatics services industry in Argentina maintain sustained growth. A recent trend is the creation of the Argentine Federation of Worker Cooperatives in Technology, Innovation and Knowledge (FACTTIC), which promotes a model based on technology development and free software. The article explores entrepreneurships from the central region to analyze their cooperative conformation, forms of work organization, working conditions and innovative initiatives. The development of these experiences is set in a context of cognitive capitalism, in his dual role of commodification of knowledge and exploitation of immaterial labor. Ongoing research is based in interviews to referents, web log analysis and secondary sources.